Contact pressure along a cross-country ski - Mössner, M.; Schindelwig, K.; Hasler, M.; Nachbauer, W. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Snow friction is a major performance factor in cross-country skiing 1. Friction is affected by ski and snow stiffness. Thus, we present a measurement method to determine the contact pressure of skis on a foundation with snow-like stiffness.